The Relationship between the Family Support System and the Creativity of Early Children 5-6 Years in Nagari Sago Salido South Coast District - Sugesty, Sherly; Ismaniar, Ismaniar (Universitas Negeri Padang, 2024)
This research was motivated by the low level of creativity of young children in the Sago Salido district, Pesisir Selatan Regency. This type of research is correlational using a quantitative approach. The population of this study was 117 parents who had children aged 5-6 years by taking a sample of 30% of the population, namely 35 people using the Disproportionate Cluster random sampling technique. The data collection technique uses a questionnaire. Data analysis techniques use percentage formulas and product moment formulas. The results of the research show that: (1) The family support system for children at home in Nagari Sago Salido can be said to be not good, this can be seen from the percentage of respondents' answers dominated by rare answers, (2) Early childhood creativity in Nagari Sago can be said to be not good This can be seen from the percentage of respondents' answers dominated by rare answers. (3) There is a significant relationship between the family support system and early childhood creativity in Nagari Sago Salido, Pesisir Selatan Regency. This can be seen from the results of the analysis using the product moment formula, that the value r = 0.974 > 0.334. So the researcher's hypothesis was accepted.Keywords: Family support system, early childhood creativity